Implementasi Hybrid App Framework dalam Membangun Aplikasi Kesehatan Mental berbasis Mobile - Muhammad Imbalo Zaki Hasibuan; Suendri Suendri (Universitas Hamzanwadi, 2023)
Currently, mental health issues in society have become an important focus, given the rise of mental issues, especially on social media. Currently, most of the use of social media is carried out using mobile technology, which also mostly uses the Android and IOS operating systems. This study aims to implement a hybrid app framework in building mobile-based mental health applications that can run on Android and IOS operating systems. The method used to build this application is the waterfall method, which is a systematic and sequential research method. The waterfall method is a step-by-step process that is well adapted to the situation in the field. The analysis is carried out through collecting data related to system needs and mental health by means of observation, interviews, and literature study. The system is designed using use case diagrams and activity diagrams. The testing phase is carried out by black box testing with the aim of finding incorrect functions, interface errors, data structure errors, performance errors, initialization errors and termination. Our findings show that the system can run well on Android and IOS operating systems, this is clarified through the results of black box testing that provides results as expected. This system is expected to be used by the wider community to help maintain mental health stability.